Answer:
[tex]3x - y = -4[/tex]
Step-by-step explanation:
To make things easier, let's first find the equation in slope-intercept form ([tex]y = mx + b[/tex] where m is the slope and b is the y-intercept.
1. Find the slope:
[tex]\frac{7 - 1}{1 - (-1)} = \frac{6}{2} = 3[/tex]
2. Find the y-intercept by plugging in (-1,1) into the equation [tex]y = 3x + b[/tex]
[tex]1 = 3(-1) + b[/tex]
so [tex]b[/tex] = 4
3. Therefore the equation of the line in slope-intercept form is [tex]y = 3x + 4[/tex]
4. To convert slope-intercept form into standard form, let's move the 3x over to the other side and divide by -1 to get rid of the negative.
Our result is [tex]3x - y = -4[/tex].
Hope this helps :)